The relationships of preventive behaviors and psychological resilience with depression, anxiety, and stress among university students during the COVID-19 pandemic: A two-wave longitudinal study in Shandong Province, China - Li, Hexian; Zhao, Jingjing; Chen, Rui; Liu, Hui; Xu, Xixing; Xu, Jing; Jiang, Xiaoxu; Pang, Mingli; Wang, Jieru; Li, Shixue; Hou, Jiaxiang; Kong, Fanlei (Frontiers in Public Health, 2023)
Study have shown that the psychological damage caused by the COVID-19 pandemic may turn into long-term health problems, so more attention should be paid to the mental health of college students. The objective of the study was to explore the longitudinal effects of protective behaviors, psychological resilience on mental health of Chinese college students during COVID-19.A total of 2948 college students from five universities in Shandong Province were included. We used the generalized estimating equations (GEE) model to estimate the impact of protective behaviors, psychological resilience on mental health.In the follow-up survey, the prevalence of Rates of anxiety (58.8% at T1 vs 41.2% at T2) and stress (23.0% at T1 vs19.6% at T2) decreased over time, while rates of depression (35.2%at T1 vs36.9% at T2) significantly increased (both p<0.001).Seniors more likely to report depression(OR=1.666,p＜0.001) ,anxiety(OR=0.815, P=0.019) and stress(OR=1.430,P=0.011). Medical students more likely to report depression(OR=1.365,P=0.021),anxiety(OR=1.303, p =0.040) and stress(OR=1.750,P=＜0.001). Compliance with wearing a mask outside is less likely to report depression (OR=0.762) and anxiety (OR=0.684). complying with the standard washing technique is less likely to report depression(OR=0.628),anxiety(OR=0.700) and stress(OR=0.637). complying with the queue is kept one meter apart is less likely to report depression (OR=0.668), anxiety (OR=0.634) and stress (OR=0.640). Psychological resilience was a protective factor for depression (OR=0.973), anxiety (OR=0.979), and stress (OR=0.974). The prevalence of depression increased and the prevalence of anxiety and stress decreased among college students during the two follow-up surveys. Senior students and medical students should receive more attention. college students should continue to follow relevant preventive behaviors. Improving psychological resilience may help maintain and promote the mental health of college students.